The processes of remediation between digital and analog artefacts to enhance student learning - Marzano Antonio (Research on Education and Media, 2023)
In recent years, numerous researches have been carried out to investigate and verify how concept maps could be effective in learning management systems. This paper discusses the use of dynamic concept maps (DCMs) as a tool to encourage remediation processes among digital artefacts and analog resources and, consequently, to enhance learning processes and improve their effectiveness. The DynaMap remediation approach (DMRA) intends to propose a possible interpretation of this process by using Vygotsky’s historical-cultural approach, enriched and contaminated by the perspective of mutual remediation of Bolter and Grusin inspired to McLuhan’s theories. The research carried out in the last five years shows how this methodology (DMRA) has positively influenced study times and learning outcomes of the engaged students.